Assessments of Irrigation Water Requirement from Deduru Oya Left Bank Canal to Supplement Deduru Oya Left Bank Irrigation Demand - Sampath, D.S.; Weerakoon, S.B.; Mishra, B.K.; Herath, S. (The Institution of Engineers, Sri Lanka, 2014)
Rainfall in Deduru Oya basin has a significant temporal variation and thus the Deduru Oya carry flash floods during rainy season and very low flows during dry season. The Deduru Oya reservoir under construction at the upstream of the existing RidiBediEla anicut will be useful to regulate discharge of the Deduru Oya for better utilizing the basin water resources especially for irrigation. The multi-purpose Deduru Oya reservoir project with a reservoir of a capacity of 75 Million Cubic Meters (MCM), augments water resources in 136 existing tank based irrigation systems in the Deduru Oya Left Bank through a Left Bank (LB) canal and also diverts water to the Iginimitiya tanking the Mee Oya basin through a Right Bank (RB)transbasin canal. This study develops a model for water management in LB canal development area and for the assessment of diversion requirement from the Deduru Oya reservoir through the LB Canal to supplement LB irrigation demand. Hydrological Engineering Center-Hydrological Modeling System (HEC-HMS) is used for runoff estimations and CROPWAT model is used to estimate crop water requirements. Water Evaluation And Planning (WEAP) model is used for water balance simulations in Deduru Oya LB canal development area and to calculate water requirements from LB canal for the period of recent 10 years. The study reveals that the annual water requirement from the LB canal for 100% cropping intensity in the proposed 3000 ha irrigable area in LB canal development area varies from 26 MCM to 41 MCM
Keywords: Irrigation Water Requirement; Deduru Oya Project; Hydrological Modeling; WEAP